Risk of Uterine Rupture with Vaginal Birth after Cesarean in Twin Gestations - Kimya Baradaran (Hindawi Limited, 2021)
Background. Women with a previous cesarean delivery may attempt a subsequent vaginal birth or repeat cesarean. Vaginal birth after cesarean carries a greater risk of uterine rupture, defined as the disruption of all uterine layers, resulting in maternal-fetal morbidity or mortality. It is unclear how the risk of uterine rupture compares in patients with twin gestations who undergo different delivery methods. Objective. The purpose of this systematic review is to determine if there is an increased risk of uterine rupture in patients with twin gestations attempting vaginal birth after cesarean (VBAC) versus planned repeat cesarean delivery (PRCD). Study Design. PubMed, Cochrane Library, and CINAHL were searched systematically. Eligible studies were prospective and retrospective studies that evaluated the incidence of uterine rupture in twin pregnancies that attempted VBAC or PRCD. Data were manually extracted from these studies, and the number of events in each group was used to calculate an odds ratio (OR) and 95% confidence interval (CI). Results. 4 retrospective studies were included with a total of 7699 participants, 2305 of whom attempted VBAC and 5394 underwent PRCD. The absolute risk of uterine rupture in the VBAC and PRCD groups was 0.87% and 0.09%, respectively. The rate of uterine rupture was significantly higher in the VBAC group than in the PRCD group (OR: 9.43; CI: 3.54-25.17). Conclusion. Although VBAC is associated with higher rates of uterine rupture in twin pregnancies when compared with PRCD, the absolute risk of uterine rupture is low in both groups. Depending on individual risk factors, vaginal birth may be offered as a safe option to women with twin pregnancies and a history of cesarean delivery.